Penerapan Bayesian Knowledge Tracing pada Game Ethno Run sebagai Media Pembelajaran Matematika Adaptif untuk Siswa Kelas 3-5 Sekolah Dasar - Alvi Setya Kurnia Dewi; Anita Qoiriah (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Mathematics is a core subject that develops critical thinking skills; however, many third to fifth-grade elementary school students face difficulties with conventional teaching methods that tend to be uniform and less adaptive. This study aims to develop and implement a mobile-based educational game,